Achieving doctorateness: Is South African higher education succeeding with graduate attributes? - Faller, F.; Burton, S.; Kaniki, A.; Leitch, A.; Ntshoe, I. (South African Journal of Higher Education, 2023)
This article applies findings from the recent national review of South African doctoral qualifications to examine ways in which universities interpret the formulation of, and apply in the context of a differentiated higher education system, the graduate attributes established in the qualification standard, in order to achieve the characteristics of “doctorateness”. The article explores the concept “graduate attributes” itself, the extent to which it is manifested in institutional, supervisory and examination practices, and how the concept is conveyed to and understood by students. National review findings indicate inconsistencies in conceptualisation and application both between and within institutions. In this article, emphasis is placed on the primary need of developing in the doctoral graduate the capacity to enter, as a deep-thinking researcher, into a community of practising peers, whether in the academy or in a profession.